Dengue fever in a south Asian metropolis: a report on 219 cases - Shiv Sekhar Chatterjee (Iranian Journal of Microbiology, 2017)
Background and Objectives: Yearly epidemics of Dengue fever occur post-monsoon in India’s capital, Delhi. A prospective observational study was conducted during the outbreak months to understand the epidemiology and outcome of this infection and its economic impact. Materials and Methods: Febrile hospitalized (n=219) patients with dengue fever diagnosed by a combination of MAC-ELISA, GAC-ELISA and NS1Antigen-ELISA were enrolled. Epidemiologic (including economic) parameters, clinical, radiological and laboratory manifestations were noted and patients followed up over the period of hospital stay. Patient management means and outcome were recorded and analysed. Results: As per WHO-2009, 153 (69.9%) and 27 (12.3%) patients were classified as dengue with warning signs and Severe Dengue respectively while according to WHO-1997 guidelines 39 (17.8%) and 18 (8.2%) patients were classified as DHF and DSS respectively. 216 patients were from the city while three were travellers; hospitalization was more frequent among the young and male gender. Fever, vomiting, aches and abdominal pain were the most common troublesome manifestations; classical dengue triad was present in 55 (25.1%) patients; hemorrhagic, neurologic and mucocutaneous manifestations were present in 44 (20.1%), 8 (3.7%) and 70 (32%) patients. Ascitis, pleural effusion, and Gall bladder wall oedema was found in 53 (24.2%), 31 (14.1%) and 45 (20.5%) patients respectively. Mortality was 1.4% (3 deaths); in addition there was an intra-uterine fetal death; mean expenditure per patient during the illness was US$ 377.25. Conclusion: Dengue virus infection results in immense morbidity and substantial mortality.